2022
DOI: 10.3390/ijerph19116547
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 8-Week In-Season Contrast Strength Training Program on Measures of Athletic Performance and Lower-Limb Asymmetry in Male Youth Volleyball Players

Abstract: Strength training using high and lower load such as contrast training (CST) seems to be beneficial as it addresses larger adaptive reserves in youth athletes. Therefore, the aim of this study was to investigate the effects of CST on dynamic balance (composite score during dynamic balance test (CS-YBT)), one repetition maximum lower-limb back squat (1RM), jumping performance (single-leg hop (SLH) or countermovement jump height (CMJ)), lower-limb asymmetry (predicted from the single-leg jump performance between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
1
0
2
Order By: Relevance
“…This study also establishes a relationship between ankle dorsiflexion and dynamic balance in athletes. This aspect supports the systematic review carried out by Mesfar et al [ 51 ], which indicates that there may be a specific association between the asymmetries of this dynamic balance and jumping performance and, on the other hand, the range of movement of the ankle and the COD tests in that involving a 180° turn. Other studies have also confirmed this, which have found significant relationships between ankle ROM and improved dynamic balance or lower body motor skills [ 52 , 53 ].…”
Section: Discussionsupporting
confidence: 88%
“…This study also establishes a relationship between ankle dorsiflexion and dynamic balance in athletes. This aspect supports the systematic review carried out by Mesfar et al [ 51 ], which indicates that there may be a specific association between the asymmetries of this dynamic balance and jumping performance and, on the other hand, the range of movement of the ankle and the COD tests in that involving a 180° turn. Other studies have also confirmed this, which have found significant relationships between ankle ROM and improved dynamic balance or lower body motor skills [ 52 , 53 ].…”
Section: Discussionsupporting
confidence: 88%
“…These results are in agreement with previous studies that found an increase in asymmetry even after a long-term training program [ 63 , 64 , 65 ]. However, contralateral asymmetry is a controversial topic in the literature because some studies have described important changes in interlimb asymmetries in young athletes after a specific training program [ 64 , 66 ], while others have found any effect [ 67 , 68 ]. The main reason for the discrepancies found among the studies seems to be the variable chosen to assess contralateral asymmetry because many contralateral neuromuscular asymmetries found throughout a season show different magnitudes and directions of change.…”
Section: Discussionmentioning
confidence: 99%
“…muscle power can be increased by explosive movements and jumping without a prefix such as in basketball and volleyball (Wang et al, 2022). Athletes need to develop leg muscle power by performing speed and acceleration movements then with specific movements in sports (Mesfar et al, 2022). Therefore, coaches certainly need to look at and consider the needs of the sport when training (Schofield et al, 2022).…”
mentioning
confidence: 99%